THE IMPLEMENTATION OF INQUIRY-BASED LEARNING STRATEGY TO ENHANCE STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT - Imansyah, Imansyah; Terasne, Terasne; Hartina, Khorida Yan (Institut Hindu Dharma Negeri Denpasar, 2019)
This research was aimed at knowing whether Inquiry-Based Learning strategy enhanced students’ writing ability in descriptive text or not. The research was a classroom action research. The data collected through quantitative and qualitative ways. Quantitative data was gained from the result of pre-test and post-test from writing test. Meanwhile, qualitative data was gained from the result of observation sheets toward students’ and teachers activity. The instrument used by the researcher were test and observation sheet. The finding of the research shows that the strategy can improve the students’ writing ability in descriptive text. the improvement can be seen from the mean score of students from pre-test, post-test one, and post-test two. The mean score of pre-test was 69.5 (35%), there were seven students who passed the minimum passing grade, in the post-test one, 72.2 (60%), twelve students passed the minimum passing grade and in the post-test two, 78.25 (85%), seventeen students passed the minimum passing grade (KKM) from twenty students.